Targeting inflammation and pro‐resolving mediators with Anetholea anisita extract to improve scalp condition. (21st September 2022) - Duroux, Romain; Baillif, Vincent; Havas, Fabien; Farge, Morgane; Maurin, Alban; Suere, Thierry; VanGoethem, Emeline; Attia, Joan
Abstract: Objective: A critical and often‐overlooked factor that may give rise to dandruff and oily hair is the intrinsic quality of the scalp stratum corneum (SC), which is often unbalanced and susceptible to external aggressions. Addressing the inflammation element of unhealthy scalp plays an important role in promoting healthy‐looking and feeling hair. Although specialized pro‐resolving lipid mediators (SPMs) have been studied in the skin to end the inflammation process and promote tissue regeneration, no studies have been provided in the scalp. This study aims to investigate SPMs expression and its role in improving scalp integrity and consequently improving hair appearance using an Anetholea anisita extract. Methods: The effect of Anetholea anisita extract was investigated in vitro on human follicle dermal papilla cells (HFDPC), evaluating its antioxidant and anti‐inflammatory properties by fluorescence staining and ELISA, respectively. Ex vivo measurement of the volume of human scalp sebaceous glands was performed using X‐ray microtomography (micro‐CT). The extract was then clinically tested on a population of dandruff sufferers presenting oily hair. Volunteers' sebum was collected on the scalp and analysed by LC–MS/MS or ELISA to identify SPMs and pro‐inflammatory markers. Scalp integrity was assessed by measuring the pH and the TEWL. Sebum production, dandruff and hair gloss were also evaluated. Result: Anetholea anisita extract reduced IL‐8 and reactive oxygen species (ROS) generation in HFDPC. Interestingly, this extract also decreased the volume of sebaceous glands as revealed by micro‐CT. This result was confirmed in vivo by a decrease in sebum production in volunteers. Moreover, SPMs were analysed and detected in the scalp for the first time. An increase in Lipoxin B4 (LxB4) and Resolvin D1 and D2 (RvD1 and RvD2) was observed after Anetholea anisita treatment as well as decrease in pro‐inflammatory sebum mediators expression such as PGE2, LTB4 and IL‐8. Consequently, the scalp barrier was reinforced as observed through improved transepidermal water loss (TEWL) and skin surface pH, reducing dandruff and improving hair health. Conclusion: The present results suggest the potential of cosmetic applications of Anetholea anisita extract to improve scalp health by targeting inflammation pathways to decrease dandruff and improve hair condition. Abstract : Anetholea anisita extract improves scalp health to improve hair conditions such as dandruff and hair brightness. This involves an action through inflammation pathways, especially on the resolution of inflammation stage. Résumé: Objectif: Un facteur important et peu étudié pouvant mener à l'apparition des pellicules ou des cheveux gras est la qualité intrinsèque du stratum corneum (SC) du cuir chevelu, souvent déséquilibré et susceptible aux agressions. L'inflammation joue un rôle clé dans l'état de santé du cuir chevelu et par conséquent du cheveu. Les médiateurs lipidiques pro‐résolution (SPMs) ont été étudiés dans la peau pour mettre fin au processus inflammatoire et promouvoir la régénération des tissus. Cependant, aucune étude n'avait été réalisée sur le cuir chevelu. Cette étude vise donc à étudier l'expression des SPMs et leurs rôles dans l'amélioration de l'intégrité du cuir chevelu et de l'apparence des cheveux en utilisant un extrait de Anetholea anisita. Méthodes: Les propriétés antioxydantes et anti‐inflammatoires de l'Anetholea anisita ont été étudiées in vitro sur les cellules papillaires folliculaires dermiques humaines (HFDPC) par fluorescence et ELISA. La mesure ex vivo du volume des glandes sébacées du cuir chevelu humain a été réalisée par microtomographie à rayons X (micro‐CT). L'extrait a ensuite été cliniquement testé sur des volontaires présentant des pellicules et des cheveux gras. Le sébum des volontaires a été prélevé sur le cuir chevelu et analysé par LC–MS/MS ou ELISA pour identifier les SPMs et les marqueurs pro‐inflammatoires. L'intégrité du cuir chevelu a ensuite été évaluée en mesurant le pH et la perte en eau transépidermique. La production de sébum, les pellicules et la brillance des cheveux ont également été évalués. Résultats: L'extrait d'Anetholea anisita a réduit la production d'IL‐8 et d'espèces réactives oxygénées sur HFDPC. Cet extrait a également diminué le volume des glandes sébacées. Ce résultat a été confirmé in vivo avec une diminution de la production de sébum chez les volontaires. De plus, les SPMs ont été analysés et détectés pour la première fois sur le cuir chevelu. Une augmentation de la Lipoxine B4 (LxB4) ainsi que des Resolvines D1 et D2 (RvD1 et RvD2) a été observée après le traitement par Anetholea anisita en plus d'une diminution de l'expression des médiateurs pro‐inflammatoires tels que PGE2, LTB4 et IL‐8. Par conséquent, la barrière du cuir chevelu a été renforcée comme observé avec une diminution de la PIE et un ajustement pH de la surface du scalp, réduisant les pellicules et améliorant la santé des cheveux. Conclusion: Les résultats obtenus montrent qu'un extrait d'Anetholea anisita permet d'améliorer la santé du cuir chevelu en ciblant les voies de l'inflammation et de la résolution permettant ainsi de renforcer la barrière du cuir chevelu, pour diminuer les pellicules et améliorer l'état des cheveux.